Folklore materials collected in Kartli (According to Iakob Gogebashvili „Dedaena“) - Nikoladze-Lomsianidze, Nora (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2019)
Ilia Chavchavadze, Akaki Tsereteli, Vazha Pshavela, Petre Umikashvili, Alexander Khakhanashvili, Tedo Razikashvili worked hard to record, assemble, publish, and scientifically study the realities of Georgian folk speech. Iakob Gogebashvili, a classic of Georgian pedagogy, publicist, children›s writer, the prominent figure of the national liberation movement, was also a collector, evaluator, savior, and user of oral „pearls“. He also laid the foundation for the teaching of folklore at school. Iakob Gogebashvili carried out folklore gathering work in his native corner, in the middle of Kartli, in the village of Variani, and he published these samples of oral tradition in the textbooks compiled by him; Such as: „Georgian alphabet“, „Nature's door“ and „mother tongue“ (in the paper we bring examples of some of them). „Mother Tongue“ is the richest in folk art among Iakob Gogebashvili's textbooks. This book was first published by the author in 1876. Gogebashvili himself recorded most of the folklore materials contained in it from the people of Kartli. These are folk poems, stories, tales, proverbs, riddles, Araks; Which played a big role in the victory of the textbook and made „Dedaena“ a public textbook. It is noteworthy that in each new edition of „Dedaeni“ the number of realities of folk speech gradually increased. For example, in the „Mother Tongue“ published in 1895, the number of oral materials reaches two hundred, while in the 1912 edition it is more than two hundred and fifty. The eminent teacher was pedagogical from the point of view of including folklore samples in the textbooks. For this purpose, he had to rewrite various folk texts. As it is indicated in the scientific literature, the oral realities collected in Kartli are included in the „Mother Tongue“ compiled by Iakob Gogebashvili in different ways. 1. Folk poems, proverbs, riddles, tales are often directly included. 2. Folklore works are used after minor content conversions. 3. Based on folk proverbs, Jacob created original children›s stories. Also, famous historical and folklore stories were used for the original works. The place of Iakob Gogebashvili, this multifaceted figure in the history of Georgian culture, is indefinable, and we would like to add that if he had created a hand-made monument - „Dedaena“, this would have been enough to immortalize his name.